2009
DOI: 10.1097/brs.0b013e318195b257
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Mechanical Load as a Risk Factor for Low Back Pain

Abstract: We found strong evidence that leisure time sport or exercises, sitting, and prolonged standing/walking are not associated with LBP. Evidence for associations in leisure time activities (e.g., do-it-yourself home repair, gardening), whole-body vibration, nursing tasks, heavy physical work, and working with ones trunk in a bent and/or twisted position and LBP was conflicting. We found no studies, thus no evidence, for an association between sleeping or sporting on a professional level and LBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(59 citation statements)
references
References 42 publications
1
56
1
1
Order By: Relevance
“…This may be because previous studies were based mainly on selfreported exposure or cohorts without frequent followup. Some studies report a positive association (8,10) but comparison with our study is highly challenged by the aforementioned different exposure measurements between studies (11,16). A few studies support our finding of lack of association between forward bending and LBP (12,37).…”
Section: Explanation (I): No Association Between Forward Bending and Lbpsupporting
confidence: 71%
See 1 more Smart Citation
“…This may be because previous studies were based mainly on selfreported exposure or cohorts without frequent followup. Some studies report a positive association (8,10) but comparison with our study is highly challenged by the aforementioned different exposure measurements between studies (11,16). A few studies support our finding of lack of association between forward bending and LBP (12,37).…”
Section: Explanation (I): No Association Between Forward Bending and Lbpsupporting
confidence: 71%
“…with technical long-term measurements of forward bending of the back over several days in a wide variety of occupational groups in different countries in order to optimize and strengthen the documentation for occupational exposure limits for forward bending of the back However, previous studies on the association between forward bending and LBP show varying results (11,16), which may be the result of shortcomings in the methods used to assess both forward bending and development and aggravation of LBP (9,11,17). Most studies have used self-reported measures of the exposure, which can be biased by current pain state, causing differential misclassification (18).…”
Section: Lagersted-olsen Et Almentioning
confidence: 99%
“…Bakker et al (2) in a literature review note that there is conflicting information about the role of a number of activities traditionally thought to contribute to LBP and the occurrence of NSLBP. This may be complicated further by the fact that the ''cause'' of NSLBP may not even have originated around the onset of symptoms, and it may have been in response to something that occurred earlier in life than the manifestations of the pain (28).…”
Section: Volume 33 | Number 1 | February 2011mentioning
confidence: 98%
“…[9]. For instance, low-magnitude, high-frequency WBV is effective at increasing bone mineral density [10]; WBV at frequencies lower than 0.5 Hz can cause motion sickness and discomfort [8]; and WBV exposure of long duration and at frequencies near the body's resonance frequency (4)(5)(6)(7)(8)(9)(10)(11)(12) transmits motion in excess of the input and can be detrimental to health [8].…”
Section: Introductionmentioning
confidence: 99%
“…Because vibration exposure occurs in many occupational and recreational activities (such as sitting and driving), many studies have been conducted to determine its health consequences [4][5][6][7]. Vibration exposure that occurs while the whole body is supported by a vibrating surface, referred to as whole-body vibration (WBV), has been found to have an effect on humans' health, activities, and comfort [8].…”
Section: Introductionmentioning
confidence: 99%